2006
DOI: 10.1590/s1517-83822006000300021
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the thermal activation of Neosartorya fischeri in pineapple and papaya nectars

Abstract: In this research factors that influence the activation of Neosartorya fischeri ascospores (heating medium, temperature of production and age of the ascospores) were studied. The heating medium used was pineapple and papaya nectars at different ratios (ºBrix/acidity). Lower activation times were observed for the N. fischeri ascospores in pineapple and papaya nectars under the conditions of temperature and production age of 25ºC for 1 month and using ratios of the heating medium of 10 for pineapple nectar and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…Other investigators reported lower spore activation (0.25e0.8 log) between 10 and 50 min with N. fischeri (E7, C3, and isolated from spoiled papaya fruit) spores in buffer at the same temperatures which is similar to our results (Amaeze & Ugwuanyi, 2011;Rajashekhara, Suresh, & Ethiraj, 1996). Slongo and Aragão (2006) found that temperature of 85 C between 10 and 20 min was required for maximum activation of N. fischeri ascospores in pineapple and papaya nectar, however the level of activated spores was not mentioned. Activation of spores has also been reported with thermal processed (105e120 C, 5e30 min) bacterial spores such as Bacillus stearothermophilus spores (Corradini, Normand, Eisenberg, & Peleg, 2010;Finley & Fields, 1962).…”
Section: Ascospore Activation and Activation Shoulderssupporting
confidence: 92%
See 1 more Smart Citation
“…Other investigators reported lower spore activation (0.25e0.8 log) between 10 and 50 min with N. fischeri (E7, C3, and isolated from spoiled papaya fruit) spores in buffer at the same temperatures which is similar to our results (Amaeze & Ugwuanyi, 2011;Rajashekhara, Suresh, & Ethiraj, 1996). Slongo and Aragão (2006) found that temperature of 85 C between 10 and 20 min was required for maximum activation of N. fischeri ascospores in pineapple and papaya nectar, however the level of activated spores was not mentioned. Activation of spores has also been reported with thermal processed (105e120 C, 5e30 min) bacterial spores such as Bacillus stearothermophilus spores (Corradini, Normand, Eisenberg, & Peleg, 2010;Finley & Fields, 1962).…”
Section: Ascospore Activation and Activation Shoulderssupporting
confidence: 92%
“…However, it has been recognized that the thermal process may activate the dormant ascospores of moulds which subsequently cause deterioration, hence resulting in economic loss (Katan, 1985;Slongo & Aragão, 2006;Splittstoesser, Nielsen, & Churey, 1993). Increasing the intensity (temperature or processing time) of the heat treatment is not desirable, due to quality reasons and consumer demands for 'fresh-like' fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of this factor on the heat inactivation of mold spores have been reported in the literature. Slongo and Aragão (2006) found that ascospore age influences the heat resistance of N. fischeri in papaya and pineapple juices. However, little information is available related to the effect of this factor on the growth of molds.…”
Section: Discussionmentioning
confidence: 98%
“…Some more heat resistant species owe their heat resistance to thick walled sexual ascospores, which can survive to thermal processes usually applied in the food production, including the production of fruit juices (23). Ascospores can be activated by the process’ temperature, being able to germinate and grow into the package during storage, reducing the product’s shelf life and causing economic losses (17). Extremely resistant species such as Byssochlamys nivea , Byssochlamys fulva , Talaromyces flavus and Neosartorya fischeri serve as standards for spore resistance and their absence indicates the quality of sterilization processes (7).…”
Section: Introductionmentioning
confidence: 99%